Research experience in the department of anatomy: A departmental analysis - D Mathivanan; M Nirmaladevi; M Jamuna (Wolters Kluwer Medknow Publications, 2020)
Background: Search and research provides the basic feed for academic knowledge across all academic departments. Research provides depth in the knowledge of a given area of exploration. One novel and interesting idea of an individual, or a team of experts, in the department and healthy, extended support from the institute can change and answer the stream of mysteries in their own field of expertise. Aim: We intend to analyze the research experience of every individual in the department of anatomy among themselves, with the department and the institute, for further improvement of research in anatomy. Methodology: 13 participants comprising 9 faculty members and 4 postgraduates were requested to answer the questionnaire composed of three sections, with questions under headings such as individual, department, and institute. Results and Conclusion: Finally, analyses were made on the responses obtained and recommendations were submitted before the department Head for necessary interventions in order to improve the research atmosphere and research outcomes in the department of anatomy.